Network Pharmacology-based Approaches Capture Essence of Chinese Herbal Medicines - Zhang, Yan-qiong; Mao, Xia; Guo, Qiu-yan; Lin, Na; Li, Shao (Chinese herbal medicines, 2016)
Traditional Chinese Medicine（TCM）, a crucial component of the current medical system, has been extensively used in clinical practice due to its valuable therapeutic efficacy, and its potentials as an important source of new pharmacophores. TCM is characterized by holistic theory, which emphasizes maintaining the balance of the patient＇s whole body using herbal formulae（fangji in Chinese） composed of mixtures of herbs with multiple bioactive ingredients. Because of the complex nature of these formulae, it is necessary to develop systematic methods to identify their bioactive ingredients and to clarify their mechanisms of action. With the rapid progress in bioinformatics, systems biology, and polypharmacology, ＂network pharmacology＂, which shifts the ＂one target, one drug＂ paradigm to the ＂network target, multi-component＂ strategy, has attracted the attention because it can not only reveal the underlying complex interactions between a herbal formula and cellular proteins but detect the influence of their interactions on the function and behavior of the system. Growing evidence shows that the network pharmacology strategy can be a powerful approach to modern research on TCM. The present paper focuses on the basis of network pharmacology and the recent progress in its methodology, illustrates its utility in screening bioactive ingredients and elucidating the mechanisms of action of TCM herbal formulae, analyzes its limitations and problems, and discusses its development direction and application prospects.